Peranan Etika Dan Tanggung Jawab Sosial Dalam Bisnis Internasional - Nur Halisah Fajarini; Hendra Ibrahim (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The inability of a country to meet the needs of its own country encourages business people to create an idea which is expected to solve this problem. One form of the idea is to do international business, with international business there will be cooperation between countries in meeting each other's needs. The existence of relationships with other countries will give rise to differences both in terms of applied business ethics and social responsibility. This research aims to determine the role of ethics and social responsibility in international business. The method used in this research is a qualitative research method that describes and explains the role of ethics and social responsibility in international business. The data collection technique used in this research is literature study, where this research is carried out by collecting data related to research originating from scientific journals and other publications that are suitable as research sources. The results of this research show that ethics and social responsibility have the same role which aims to improve the company's image and develop the company. A business will not be able to develop well without the role of consumers, because the company's main goal, apart from making a profit, is to attract consumer interest and gain trust and build a good image from consumers and business partners.